The impact of high-intensity interval training on metabolic syndrome - Greeley, S. J.; Martinez, N.; Campbell, B. I. (Strength and Conditioning Journal, 2013)
Metabolic syndrome is a cluster of risk factors specific to cardiovascular disease. Various exercise methods have been prescribed to treat these risk factors. However, research suggests that exercise intensity may play a vital role in effective reversal of metabolic syndrome. Therefore, low-volume high-intensity interval training offers an attractive exercise prescription.